The Intertwined Effects of Hydrographic Barriers, Palaeoclimate and Life History on Genetic Structure of Marine Populations: A Case Study of Two Marine Invertebrates - KALKAN TEZCAN, Evrim; HEMOND, ELIZABETH MATHER; KARHAN , SELAHATTIN ÜNSAL; BILGIN, RAŞIT (Mediterranean Marine Science, 2023)
Marine organisms with pelagic planktonic larval stages have high dispersal potential, yet their ranges are restricted by present and historical geographic and oceanographic features. Hydrogeographic features, such as straits and water current patterns, as well as paleoclimate can affect population connectivity, genetic differentiation, and ultimately speciation, but species distributions are also affected by life history characteristics. This study evaluates the effect of the Turkish Straits System (TSS) on the genetic differentiation of two benthic invertebrates with pelagic larvae, the Mediterranean mussel, Mytilus galloprovincialis, and the rockpool prawn, Palaemon elegans, using mitochondrial and nuclear markers (microsatellites for M. galloprovincialis and Histone H3 gene for P. elegans). For both species, the mitochondrial DNA analyses separated the Black Sea and the Eastern Mediterranean (Aegean and Levantine seas) populations into two clusters. In contrast, in both species the nuclear data indicated no differentiation between Black Sea and Eastern Mediterranean populations. The results suggest that for both species, some individuals of Black Sea origin moved south, most likely through the transport of their pelagic larvae via the surface currents of the TSS. However, for the most part, individuals of Mediterranean origin (from Aegean and Levantine seas) were not able to successfully migrate in the opposite direction, though the small differences in the frequencies of migration in this direction indicate the effects of the life history characteristics of the two species on genetic structure.